Mechanism design without quasilinearity - Tomoya Kazumura; Debasis Mishra; Shigehiro Serizawa (Theoretical Economics, 2020)
This paper studies a model of mechanism design with transfers where agents' preferences need not be quasilinear. In such a model, (1) we characterize dominant strategy incentive compatible mechanisms using a monotonicity property; (2) we establish a revenue uniqueness result: for every dominant strategy implementable allocation rule, there is a unique payment rule that can implement it; and (3) we show that every dominant strategy incentive compatible, individually rational, and revenue-maximizing mechanism must charge zero payment for the worst alternative (outside option). These results are applicable in a wide variety of problems (single object auction, multiple object auction, public good provision etc.) under suitable richness of type space. In particular, our results are applicable to two important type spaces: (a) type space containing an arbitrarily small perturbation of quasilinear type space and (b) type space containing all positive income effect preferences.
Keywords: D80; D44; D40; 330; Incentive compatibility; individual rationality; monotonicity; non-quasilinear preferences; revenue equivalence